Inovasi Desain Produk Melalui Metode Double Diamond Pada Alat Pembelajaran Kelompok Tunanetra Berbasis Rantai Makanan - Putri Sary; Ghia Tri Jayanti; R. Moch . Rizal Hafiyan; Insani Handayani Madania (Jurnal Desain Produk Nasional, 2025)
Special education, such as Special Schools, is in the spotlight of the community because of the lack of fulfillment of educational allowances. It is not only a matter of theoretical fulfillment, but also the lack of special learning support tools that are not in the form of general education products. The purpose of this study is to produce a product design that can help children with special needs in the visually impaired group according to the learning outcomes and independence of students. This study uses the double diamond method that produces products with the criteria of the results of the evaluation of previous educational products. Answering this problem, the researcher used a previous study and obtained a pyramid triangle equipped with Braille text according to the characters and a brief design of the field study. Keywords: Children with Special Needs, Blindness, Previous Studies, Educational Products